Cu-coated Ni3Se2-coated NiSe / NF multifunctional electrode material and preparation method thereof
By preparing Cu@Ni3Se2@NiSe/NF multifunctional electrode material, the problem of lack of materials in the prior art that have both SOR, HER and ORR electrocatalytic activities is solved, and high-efficiency and low-energy consumption hydrogen production and sulfur recovery are achieved.
Patent Information
- Application Number
- CN202411859487.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-17
AI Technical Summary
There is a lack of multifunctional electrode materials that can simultaneously have electrocatalytic activities of sulfur ion oxidation reaction (SOR), hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR), resulting in high system complexity and cost.
Cu@Ni3Se2@NiSe/NF multifunctional electrode material was used, which was prepared by hydrothermal method and electrochemical deposition method. The Ni3Se2@NiSe heterostructure was constructed and copper particles were uniformly anchored on its surface to form a composite material.
The catalytic activity and efficiency of HER, SOR, and ORR are significantly improved, the overpotential is reduced, the stability and reliability of the electrocatalyst is improved, and low-energy consumption of hydrogen production and sulfur recovery are achieved.
Smart Images

Figure CN119776888A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a Cu@Ni3Se2@NiSe / NF multifunctional electrode material and a preparation method thereof. Background Art
[0002] As a clean energy, hydrogen plays a huge role in combating global warming and climate change. Hydrogen production by water electrolysis is an effective and convenient hydrogen production scheme. The splitting of water includes two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). However, OER has a high thermodynamic barrier and requires a high potential (>1.23V) to drive the entire water splitting system, which results in huge power consumption. Therefore, it is urgent to find some strategies to achieve low-cost and safe hydrogen production.
[0003] First, from the perspective of reducing internal energy consumption, using the more thermodynamically favorable sulfur ion oxidation reaction (SOR) and hydrogen evolution reaction (HER) to replace the traditional oxygen evolution reaction (OER) is one of the effective strategies to achieve energy conservation goals. SOR not only has faster kinetic characteristics, but also can convert sulfur ions in sulfur-containing wastewater into polysulfides as easily oxidizable electron donors, thereby realizing sulfur resource recovery.
[0004] In the traditional water electrolysis process (i.e., OER||HER), a large number of bubbles generated on the surface of the cathode catalyst will block the electrode surface, causing kinetic, ohmic and mass transfer polarization phenomena; in addition, the simultaneous release of hydrogen (H2) and oxygen (O2) may also form a flammable and explosive mixed gas. In contrast, in the SOR||HER system, since the SOR process does not generate any gas byproducts, it can effectively avoid the formation of bubbles on the electrode and the various problems it brings, thereby achieving the purpose of low-energy hydrogen production and sulfur recovery. Secondly, from the perspective of external energy supply, although the total energy consumption of the SOR||HER coupling system in hydrogen production is significantly lower than that of the conventional water electrolysis system, its operation still requires a certain amount of energy support. This demand has promoted the advancement of chemical batteries and energy conversion technologies.
[0005] Zinc-air battery (ZAB) is a highly potential electrochemical energy storage device, which has been highly valued by the academic community due to its low cost, high energy density, safety and high efficiency. This type of battery uses oxygen in the atmosphere as the positive electrode active material for oxygen reduction reaction (ORR), and uses metallic zinc as the negative electrode active material, forming an innovative chemical power source. Based on the above principle, we can design a SOR||HER system driven by zinc-air batteries, which is completely independent of other external energy supplies, and can achieve the dual goals of sulfur recovery and efficient hydrogen production.
[0006] Building a zinc-air battery to drive the SOR||HER coupling system is an ingenious strategy to achieve sulfur recovery and efficient hydrogen production. However, this approach also faces several challenges. Ensuring the effective conduct of the three half reactions of HER, SOR, and ORR is the core of the successful operation of the system. All three half reactions rely on efficient electrocatalysts, and the use of single-function catalysts may not only increase the complexity of the system, but also increase manufacturing costs. Therefore, it is particularly important to find a high-performance multifunctional electrode material that can simultaneously promote HER, SOR, and ORR reactions.
[0007] Although some precious metals such as platinum, palladium, and rhodium have excellent electrocatalytic properties, their high prices limit their widespread application on an industrial scale; although some transition metal catalysts show good activity, they often have the problem of easy aggregation and poor conductivity. Summary of the invention
[0008] The problem in the prior art is that the multifunctional electrode materials that have SOR, HER and ORR electrocatalytic activities have high overpotential and poor catalytic activity. In view of the above technical problems, the present invention provides a Cu@Ni3Se2@NiSe / NF multifunctional electrode material, and the preparation method thereof comprises the following steps:
[0009] (1) removing the oxide film and impurities on the surface of the porous nickel foam to obtain a nickel foam carrier;
[0010] (2) adding a nickel source, urea and ammonium fluoride to deionized water, stirring to obtain a mixed solution, and transferring the mixed solution to a hydrothermal reactor, and then completely immersing the nickel foam carrier obtained in step (1) into the solution in the hydrothermal reactor, and then performing a hydrothermal reaction at 100-140° C. After the hydrothermal reaction is completed, cooling to room temperature, washing the reaction solution with deionized water and anhydrous ethanol at least 3 times in sequence, and obtaining Ni(OH)2 / NF after drying;
[0011] (3) first dissolving the reducing agent in deionized water, then adding the selenium source, stirring for at least 30 minutes, and then transferring to a hydrothermal reactor, completely immersing the Ni(OH)2 / NF obtained in step (2) in the solution in the hydrothermal reactor, and then performing a hydrothermal reaction at 105-145°C. After the reaction is completed, naturally cooling to room temperature, the reaction solution is washed with deionized water and anhydrous ethanol at least 3 times, and dried to obtain Ni3Se2@NiSe / NF;
[0012] (4) The divalent copper salt, nitric acid (mass concentration of 65%) and deionized water are uniformly mixed to obtain an electrochemical deposition solution, and the Ni3Se2@NiSe / NF obtained in step (3) is completely immersed in the electrochemical deposition solution. The copper ions in the electrochemical deposition solution are reduced and deposited on the surface of the Ni3Se2@NiSe / NF by an electrochemical deposition method. After the reaction is completed, the Ni3Se2@NiSe / NF is washed with deionized water and anhydrous ethanol for at least 3 times in sequence, and dried to obtain Cu@Ni3Se2@NiSe / NF.
[0013] Preferably, the method of step (1) is as follows:
[0014] The porous nickel foam is sequentially immersed in hydrochloric acid, anhydrous ethanol and deionized water for ultrasonic cleaning for at least 30 minutes, and then vacuum dried to obtain a nickel foam carrier.
[0015] Preferably, the concentration of the hydrochloric acid is 3 mol / L.
[0016] Preferably, in step (2), the usage ratio of the nickel source, urea, ammonium fluoride and deionized water is 840-890 mg: 270-310 mg: 80-110 mg: 10-30 mL.
[0017] Preferably, in step (3), the ratio of the selenium source to deionized water is 75-120 mg: 15-30 mL.
[0018] Preferably, the hydrothermal reaction time in step (2) is 10-14 h.
[0019] Preferably, the hydrothermal reaction time in step (3) is 9-14 h.
[0020] Preferably, the nickel source includes one or more of Ni(NO3)2·6H2O, NiSO4·6H2O, and NiCl2·6H2O.
[0021] Preferably, the selenium source includes one or more of Se, SeO2, and Na2SeO3.
[0022] Preferably, the reducing agent is sodium borohydride and / or hydrazine hydrate.
[0023] Preferably, the divalent copper salt includes one or more of Cu(SO4)2·5H2O, CuCl2·2H2O, and Cu(NO3)2·6H2O.
[0024] Preferably, the method of step (4) is as follows:
[0025] The electrochemical deposition method adopts a three-electrode system, with Ni3Se2@NiSe / NF electrode material as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode, and electrochemical deposition is performed under constant current.
[0026] The present invention has the following beneficial effects:
[0027] (1) The present invention selectively selects transition metal selenides as the main active components of the catalyst. Selenides have unique 4s 2 p 4 The electronic structure and empty 3d orbital can form a strong metal bond with transition metals, which not only gives selenides excellent crystallization properties and intrinsic catalytic activity, but also promotes the effective transfer of electrons in the electrocatalytic process, thereby significantly improving the electrocatalytic efficiency. In addition, transition metal selenides are diverse and abundant in resources, and their cost is much lower than that of expensive precious metal catalysts, providing economic advantages for practical applications. More importantly, selenides have the ability to selectively convert sulfur ions into polysulfides, avoiding the catalyst poisoning caused by sulfur ions in the SOR process, and ensuring the stability and reliability of the catalyst in long-term operation.
[0028] (2) The present invention successfully constructs a Ni3Se2@NiSe heterostructure on the surface of nickel foam and cleverly anchors metal copper (Cu) particles uniformly on the structure. The formation of this multiphase interface not only promotes the effective electron transfer between Cu and Ni3Se2@NiSe, but also significantly improves the adsorption behavior of key intermediates in the HER, SOR, and ORR processes through multi-site synergy. This design fundamentally improves the intrinsic activity of the catalyst;
[0029] (3) Cu@Ni3Se2@NiSe / NF is a composite material composed of nanorod-shaped Ni3Se2@NiSe / NF structure and Cu particles synthesized on a nickel foam substrate by in-situ growth. Thanks to the presence of Cu micron particles in a metallic and highly dispersed form, this material exhibits significant metal-support interaction, thereby promoting charge redistribution in the interface region. This feature can not only effectively improve the activity and stability of the electrocatalytic active sites, but also the design of the three-dimensional nickel foam substrate helps to maintain the overall structure of the catalyst, enhance the conductive properties of the material, and effectively avoid the aggregation of catalyst particles.
[0030] (4) Through research, the present invention found that the catalytic activity of the obtained Cu@Ni3Se2@NiSe / NF electrode material is closely related to the time of constant current electrochemical deposition. When the current is 0.1A and the electrochemical deposition time is 10min, the HER and SOR performances of the obtained Cu@Ni3Se2@NiSe / NF electrode material are optimal and the overpotential is minimal. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : This is the SEM image of Cu@Ni3Se2@NiSe / NF-1 electrode material.
[0032] Figure 2 : These are the XRD patterns of Cu@Ni3Se2@NiSe / NF-1, Ni(OH)2 / NF, and Ni3Se2@NiSe / NF.
[0033] Figure 3 : This is a comparison chart of HER and SOR performance tests of Cu@Ni3Se2@NiSe / NF-1, Ni(OH)2 / NF, Ni3Se2@NiSe / NF, Cu@Ni3Se2@NiSe / NF-2, and Cu@Ni3Se2@NiSe / NF-3.
[0034] Figure 4 : This is the LSV test comparison diagram of Cu@Ni3Se2@NiSe / NF-1 in HER||SOR and HER||OER coupling systems, as well as the LSV curve diagram of the ORR performance test of Cu@Ni3Se2@NiSe / NF-1.
[0035] Figure 5 : This is a diagram of the hydrogen production effect of the SOR||HER system of the zinc-air battery self-driven Cu@Ni3Se2@NiSe / NF-1 as the electrode material, as well as a linear diagram of the hydrogen production Faraday efficiency and time. DETAILED DESCRIPTION
[0036] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0037] The porous nickel foam in the following embodiments of the present invention was purchased from Xingzhenghong Technology Co., Ltd. with the item number XZH202201N.
[0038] The porous nickel foam used in the following examples of the present invention has a length of 1.5 cm, a width of 1.0 cm and a thickness of 0.1 cm.
[0039] Example 1
[0040] A Cu@Ni3Se2@NiSe / NF multifunctional electrode material, the preparation method of which is as follows:
[0041] (1) immersing the porous nickel foam in hydrochloric acid, anhydrous ethanol, and deionized water in sequence for ultrasonic cleaning for 30 min, and then vacuum drying at 60° C. to obtain a nickel foam carrier, wherein the concentration of the hydrochloric acid is 3 M;
[0042] (2) 872.2 mg Ni(NO3)2·6H2O, 303.3 mg urea, and 96.46 mg ammonium fluoride were added to 20 mL deionized water, stirred evenly to obtain a mixed solution, and transferred to a hydrothermal reactor, and then the foamed nickel support obtained in step (1) was completely immersed in the solution in the hydrothermal reactor, and then a hydrothermal reaction was carried out at 120°C for 12 hours. After the hydrothermal reaction was completed, the reaction solution was cooled to room temperature, and the reaction solution was washed with deionized water and anhydrous ethanol for three times respectively, and dried at 60°C to obtain Ni(OH)2 / NF;
[0043] (3) First, hydrazine hydrate was dissolved in 20 mL of deionized water, and then 100 mg of Na2SeO3 was added, stirred for 30 min, and then transferred to a hydrothermal reactor, and the Ni(OH)2 / NF obtained in step (2) was completely immersed in the solution in the hydrothermal reactor, and then a hydrothermal reaction was carried out at 120° C. for 12 h. After the reaction was completed, it was naturally cooled to room temperature, and the reaction solution was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 60° C. to obtain Ni3Se2@NiSe / NF;
[0044] (4) 25 mmol CuCl2·2H2O, 1.5 mL nitric acid (mass concentration of 65%) and 50 mL deionized water were mixed to obtain an electrochemical deposition solution, and the Ni3Se2@NiSe / NF obtained in step (3) was completely immersed in the electrochemical deposition solution. The Ni3Se2@NiSe / NF was electrochemically deposited at a current of -0.1 A for 10 min using a three-electrode system with Ni3Se2@NiSe / NF as the working electrode, platinum wire as the counter electrode and Ag / AgCl as the reference electrode. After the reaction was completed, the working electrode was washed three times with deionized water and anhydrous ethanol respectively, and dried to obtain Cu@Ni3Se2@NiSe / NF-1.
[0045] The SEM of the Cu@Ni3Se2@NiSe / NF-1 electrode material is shown in the attached manual. Figure 1 shown. Figure 1 (a) shows that Cu@Ni3Se2@NiSe / NF-1 is evenly distributed on the nickel foam skeleton, which better maintains the integrity of the nickel foam skeleton. Figure 1 (b) Surface Cu microparticles are uniformly anchored on Ni3Se2@NiSe / NF. Figure 1 (c) shows that Ni3Se2@NiSe / NF presents a unique nanoball-rod structure. This three-dimensional nanoball-rod structure not only increases the number of exposed active sites, but also promotes the effective adsorption of intermediates, thereby significantly improving the electrocatalytic performance of the material.
[0046] Comparative Example 1 is the Ni(OH)2 / NF obtained in Example 1.
[0047] Comparative Example 2 is the Ni3Se2@NiSe / NF obtained in Example 1.
[0048] The XRD patterns of Cu@Ni3Se2@NiSe / NF-1, Ni(OH)2 / NF and Ni3Se2@NiSe / NF are shown in the attached manual. Figure 2 shown.
[0049] Example 2 is the same as Example 1, except that the electrochemical deposition time in Example 2 is 5 min. The obtained electrode material is recorded as Cu@Ni3Se2@NiSe / NF-2.
[0050] Example 3 is the same as Example 1, except that the electrochemical deposition time in Example 3 is 15 min. The obtained electrode material is recorded as Cu@Ni3Se2@NiSe / NF-3.
[0051] Instructions attached Figure 3 Linear sweep voltammetry was used to evaluate the catalytic activity of the electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 in HER and SOR, respectively. The tests all used a three-electrode system (the counter electrode was a platinum electrode, the reference electrode was an Ag / AgCl electrode, and the working electrodes were the electrode materials obtained in Examples 1-3 and Comparative Examples 1-2, respectively). The electrolyte for HER was a 1.0M NaOH aqueous solution, and the electrolyte for SOR was a mixed solution formed by dissolving 1 mol NaOH and 1 mol Na2S solid in 1L deionized water. Different catalysts were tested at 100 mA·cm -2 The overpotential η test results of SOR and HER under different current densities are shown in Table 1.
[0052] Table 1
[0053]
[0054] As shown in Table 1, the HER and SOR performances of Cu@Ni3Se2@NiSe / NF-1, Ni3Se2@NiSe / NF-2, and Cu@Ni3Se2@NiSe / NF-3 are much better than those of Ni(OH)2 / NF. The reason is that metal selenides have better conductivity than hydroxides, and the s and p orbitals of Se elements are easy to hybridize with the d orbitals of Ni, thus giving Ni3Se2@NiSe / NF excellent crystallinity and catalytic activity. At the same time, Cu@Ni3Se2@NiSe / NF-1 exhibits more excellent catalytic performance, which is due to the synergistic effect between metal Cu and Ni3Se2@NiSe / NF substrate, making Cu exist in a more highly dispersed metallic state, thereby enhancing the catalytic activity of HER and SOR and the stability of the electrode material in alkaline electrolyte. In addition, the duration of electrodeposition also has an important influence on the performance of the catalyst. Experimental results show that the Cu@Ni3Se2@NiSe / NF-1 electrode material treated with 10 minutes of electrodeposition has better electrocatalytic activity than Cu@Ni3Se2@NiSe / NF-2 and Cu@Ni3Se2@NiSe / NF-3.
[0055] Application Example 1
[0056] (1) Construction of HER||SOR coupling system performance: Cu@Ni3Se2@NiSe / NF-1 was used as the cathode electrode and anode electrode of the H-type electrolytic cell, respectively, to construct a two-electrode system for testing. The cathode electrolyte was a 1.0 M NaOH aqueous solution, and the anode electrolyte was a mixed solution of 1 mol NaOH and 1 mol Na2S solid dissolved in 1 L of deionized water. The diaphragm was a cationic membrane (DuPont, Nafion 117), which was Na + The transport of ions provides channels to maintain ionic charge balance and divide the anode / cathode regions. Linear sweep voltammetry tests were performed at a voltage of 0-2.5 V (relative to Ag / AgCl), and the test results were compensated with 90% infrared.
[0057] (2) Performance of HER||OER coupling system: The test was conducted on a CHI660E electrochemical workstation, using the Cu@Ni3Se2@NiSe / NF-1 obtained in Example 1 as the working electrode, the platinum electrode as the counter electrode, and the cathode and anode electrolytes were both 1.00 M NaOH aqueous solution. The HER||OER coupling system was tested at 5 mV·s in the range of 1.2-2.0 V (relative to Ag / AgCl). -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.
[0058] The instruction manual is attached Figure 4(a) is a comparison of the LSV tests of the HER||SOR and HER||OER coupling systems. The results show that at 100 mA cm -2 At a current density of , the HER||SOR coupling system only requires a voltage of 0.656 V to reach the corresponding current density, while the HER||OER system requires a voltage of 1.783 V, and the energy consumption is much higher than that of the HER||SOR system.
[0059] (3) Oxygen reduction reaction performance:
[0060] Preparation of ink: The Cu@Ni3Se2@NiSe / NF-1 catalyst obtained in Example 1 was completely immersed in anhydrous ethanol and ultrasonicated for 6 hours. Subsequently, the Cu@Ni3Se2@NiSe powder separated after ultrasonication was collected and dried at 60°C to finally obtain Cu@Ni3Se2@NiSe powder. Accurately weigh 4 mg of Cu@Ni3Se2@NiSe powder and place it in a small centrifuge tube, and ultrasonically mix it evenly with 600 μL of deionized water, 320 μL of isopropanol, and 80 μL of a 5% Nafion aqueous solution.
[0061] Oxygen reduction reaction linear sweep voltammetry test: The test was conducted on a CHI 660E electrochemical workstation. In a three-electrode system, 9.4 μL of the above ink was evenly applied on the surface of a clean glassy carbon electrode. After the ink dried, the glassy carbon electrode with the catalyst was used as the working electrode, the platinum electrode as the counter electrode, and Ag / AgCl as the reference electrode. The electrolyte was a 0.1 M KOH aqueous solution. The LSV test of ORR was conducted on a RRDE rotating ring disk electrode. Before the test, oxygen (oxygen, purity 99.99%) was passed through the electrolyte for 30 minutes to ensure that the electrolyte reached an oxygen saturation state. The scan rate was 5 mV·s in the voltage range of -0.9-0.2 V (relative to Ag / AgCl). -1 , the LSV curve was tested at a speed of 1200 rpm.
[0062] Instructions attached Figure 4 (b) is the LSV curve of the ORR performance test of Cu@Ni3Se2@NiSe / NF-1 electrode material. It can be seen from the figure that the half-wave potential of the electrode material reaches 0.728V, which indicates that it has good ORR catalytic activity. Based on this performance, Cu@Ni3Se2@NiSe / NF-1 can be used as an ORR catalyst for the cathode of zinc-air batteries to power the SOR||HER coupling system, thereby achieving efficient and low-energy sulfur removal and hydrogen production.
[0063] Application Example 2
[0064] (1) Assembly of zinc-air battery
[0065] Prepare 20 mg mL -1 The ink was prepared by accurately weighing 20 mg of the Cu@Ni3Se2@NiSe / NF powder obtained in Example 1, mixing it with 600 μL of deionized water, 320 μL of isopropanol, and 80 μL of a 5% Nafion aqueous solution, and ultrasonically homogenizing it. 100 μL of the ink was evenly dropped on a 1.0 cm × 1.0 cm carbon paper, and air-dried naturally as the positive electrode, a 0.5 cm × 3 cm zinc sheet that was polished and smooth was used as the negative electrode, and a uniform mixture of 7 mL of a 6 M KOH aqueous solution and 0.2 mol Zn(OAc)2·2H2O was used as the electrolyte to assemble a zinc-air battery.
[0066] (2) Assembly of the zinc-air battery self-driven SOR||HER system
[0067] Use wires to connect two zinc-air batteries in series and the SOR||HER coupling system to form a self-driven SOR||HER system. The carbon paper (positive electrode) is connected to the anode of the electrolytic cell to produce a SOR reaction, and the zinc sheet (negative electrode) is connected to the cathode of the electrolytic cell to produce a HER reaction. Among them, the zinc-air battery can output electrical energy as the power source of the self-driven system, drive the production of hydrogen and the degradation of sulfides, and realize the effective operation of the self-driven system without external energy.
[0068] Instructions attached Figure 5 (a) is a volume record of hydrogen collected by the drainage method within 90 minutes on the cathode side of the successfully assembled zinc-air battery-driven SOR||HER system. Figure 5 (b) is the relationship between the actual hydrogen production at the cathode and time. It can be seen that within 90 minutes, the self-driving system can stably supply energy to the SOR||HER system and maintain stable hydrogen production.
[0069] In summary, the Cu@Ni3Se2@NiSe / NF-1 trifunctional catalyst synthesized in the present invention has excellent HER, SOR, and ORR performances, and can successfully drive the zinc-air battery to supply energy for the SOR||HER coupling system, which makes the present invention show great potential and development prospects in the application field of self-driven hydrogen production and sulfur removal of zinc-air batteries.
[0070] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A Cu@Ni3Se2@NiSe / NF multifunctional electrode material, characterized in that: The preparation method comprises the following steps: (1) removing the oxide film and impurities on the surface of the porous nickel foam to obtain a nickel foam carrier; (2) adding a nickel source, urea and ammonium fluoride to deionized water, stirring to obtain a mixed solution, and transferring the mixed solution to a hydrothermal reactor, and then completely immersing the nickel foam carrier obtained in step (1) into the solution in the hydrothermal reactor, and then performing a hydrothermal reaction at 100-140° C. After the hydrothermal reaction is completed, cooling to room temperature, washing the reaction solution with deionized water and anhydrous ethanol at least 3 times in sequence, and obtaining Ni(OH)2 / NF after drying; (3) first dissolving the reducing agent in deionized water, then adding the selenium source, stirring for at least 30 minutes, and then transferring to a hydrothermal reactor, completely immersing the Ni(OH)2 / NF obtained in step (2) in the solution in the hydrothermal reactor, and then performing a hydrothermal reaction at 105-145°C. After the reaction is completed, naturally cooling to room temperature, the reaction solution is washed with deionized water and anhydrous ethanol at least 3 times, and dried to obtain Ni3Se2@NiSe / NF; (4) Mixing divalent copper salt, nitric acid and deionized water to obtain an electrochemical deposition solution, completely immersing the Ni3Se2@NiSe / NF obtained in step (3) into the electrochemical deposition solution, reducing the copper ions in the electrochemical deposition solution and depositing them on the surface of the Ni3Se2@NiSe / NF by electrochemical deposition, and washing with deionized water and anhydrous ethanol at least 3 times in sequence after the reaction is completed, and drying to obtain Cu@Ni3Se2@NiSe / NF.
2. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The method of step (1) is as follows: The porous nickel foam is sequentially immersed in hydrochloric acid, anhydrous ethanol and deionized water, respectively, ultrasonically cleaned for at least 30 minutes, and then vacuum dried to obtain a nickel foam carrier.
3. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 2, characterized in that: The concentration of the hydrochloric acid is 3 mol / L.
4. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: In step (2), the usage ratio of the nickel source, urea, ammonium fluoride and deionized water is 840-890 mg: 270-310 mg: 80-110 mg: 10-30 mL.
5. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: In step (3), the usage ratio of selenium source to deionized water is 75-120 mg:15-30 mL.
6. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The nickel source includes one or more of Ni(NO3)2·6H2O, NiSO4·6H2O, and NiCl2·6H2O.
7. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The selenium source includes one or more of Se, SeO2, and Na2SeO3.
8. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The reducing agent is sodium borohydride and / or hydrazine hydrate.
9. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The divalent copper salt includes one or more of Cu(SO4)2·5H2O, CuCl2·2H2O, and Cu(NO3)2·6H2O.
10. The Cu@Ni3Se2@NiSe / NF multifunctional electrode material according to claim 1, characterized in that: The method of step (4) is as follows: The electrochemical deposition method adopts a three-electrode system, with Ni3Se2@NiSe / NF electrode material as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The electrochemical deposition is performed under constant current, the current size is 0.1A, and the electrochemical deposition time is 5-15min.
Citation Information
Patent Citations
Biphase nickel selenide difunctional electrolyzed water catalyst as well as preparation method and application thereof
CN113637986A
Amorphous nickel hydroxide nanotube wrapped Cu nanoparticle heterostructure material, preparation method and application thereof
CN114892209A
Self-electricity-synchronous high-efficiency sulfur removal and hydrogen production method based on catalytic driving
CN118561381A